2013
DOI: 10.1074/jbc.m113.500561
|View full text |Cite
|
Sign up to set email alerts
|

The Prometastatic Ribosomal S6 Kinase 2-cAMP Response Element-binding Protein (RSK2-CREB) Signaling Pathway Up-regulates the Actin-binding Protein Fascin-1 to Promote Tumor Metastasis

Abstract: Background: RSK2-mediated prometastatic signaling mechanism remains unclear. Results: RSK2-CREB pathway up-regulates Fascin-1 to promote filopodia formation, cancer cell invasion, and tumor metastasis. Conclusion: RSK2-CREB-Fascin-1 pathway could be a promising therapeutic target in metastatic cancers. Significance: These data will advance our understanding of signaling pathways that mediates RSK2-dependent prometastatic signals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 45 publications
0
38
0
Order By: Relevance
“…Kang et al (46) reported that silencing RSK2 decreased metastatic colonization to the lymph nodes using a human head and neck squamous cell carcinoma line. They further followed up on these observations using the RSK CTKD inhibitor, FMK-MEA, which resulted in a modest decrease in metastatic tumor burden from 97% to 79% (47). In a screen Lara et al (48) identified that loss of RSK1 increased motility in lung cancer lines but in contrast Zhou et al (49) found that inhibition of RSK activity was associated with decreased motility in lung cancer lines.…”
Section: Discussionmentioning
confidence: 99%
“…Kang et al (46) reported that silencing RSK2 decreased metastatic colonization to the lymph nodes using a human head and neck squamous cell carcinoma line. They further followed up on these observations using the RSK CTKD inhibitor, FMK-MEA, which resulted in a modest decrease in metastatic tumor burden from 97% to 79% (47). In a screen Lara et al (48) identified that loss of RSK1 increased motility in lung cancer lines but in contrast Zhou et al (49) found that inhibition of RSK activity was associated with decreased motility in lung cancer lines.…”
Section: Discussionmentioning
confidence: 99%
“…IHC analysis of GDH1 expression was performed according to the protocol described previously (Li et al, 2013). Approval of use of human specimens was given by the Institutional Review Board of Emory University.…”
Section: Methodsmentioning
confidence: 99%
“…In normal prenatal pig skeletal muscle, FSCN1 expression increases during major muscle developmental spurts, but postnatally it is expressed highly only in brain tissues during accelerated neural cell development [133] . The CREB pathway is often activated in different metastatic human cancers, causing the upregulation of FSCN1 expression [134] . In HNSCC patients, expression of RSK2 and FSCN1 proteins correlate closely.…”
Section: Cell Factors Deregulated In Cancer By Myomirsmentioning
confidence: 99%